2011
DOI: 10.1055/s-0031-1280019
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis at Different Vacuum Levels during Vacuum-Assisted Venous Drainage: A Prospective Randomized Clinical Trial

Abstract: Constant negative suction at -80 mmHg during elective coronary bypass operations caused more hemolysis. We do not recommend a constant suction of -80 mmHg for VAVD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…As the ECC becomes an arteriovenous extension of the patient's vascular network, the arterial flow and venous flow of the ECC must be in equilibrium. This constant ensures an adequate arteriovenous systemic flow capable of satisfying the patient's physiological needs during ECC [18][19][20][21][22].…”
Section: Optimisation Of the Circuit And The Cpb Console With A Holdementioning
confidence: 99%
“…As the ECC becomes an arteriovenous extension of the patient's vascular network, the arterial flow and venous flow of the ECC must be in equilibrium. This constant ensures an adequate arteriovenous systemic flow capable of satisfying the patient's physiological needs during ECC [18][19][20][21][22].…”
Section: Optimisation Of the Circuit And The Cpb Console With A Holdementioning
confidence: 99%
“…Roller pump, kinetic, and vacuum-assisted venous drainage have been reported, each with unique considerations for cardiopulmonary bypass [119][120][121][122][123][124][125][126][127][128][129][130][131][132][133]. Venous return is visually monitored through out the bypass run and quantified by changes in the venous reservoir level.…”
Section: Standard and Augmented Venous Returnmentioning
confidence: 99%
“…VAVD increases the external arterial line filter purge and/or sampling line shunt flow and increases the rate of transfusion when adding volume to the reservoir (blood, crystalloid and medications) [124]. And, excessive negative pressure may damage the formed elements of the blood [127]. Further, the displayed roller head arterial pump output may be inaccurate with negative pressure values below −50 mmHg [126].…”
Section: Vacuum-assisted Venous Drainagementioning
confidence: 99%
“…2 However, we should be careful when applying negative pressure because excessive negative pressure may induce air embolism in the circuit [3][4][5][6] or hemolysis. 7,8 Many important studies have examined these problems; however, few studies have suggested a safe negative pressure to minimize hemolysis in infants. Therefore, we examined the hemolysis associated with negative pressure during VAVD maneuver in the perioperative period in children weighing less than 10 kg.…”
Section: Introductionmentioning
confidence: 99%